Evaluación de los riesgos asociados al proceso productivo y su incidencia en los trabajadores de la empresa textil, Hilandería de la parroquia salinas. - Rea Guambuguete, Alexis Stalyn (2020)
The present research project called "Evaluation of the risks associated with the production process and their impact on the workers of the textile company, spinning mill of the Salinas parish" had as its main objective to assess the occupational risks associated with the production process and their impact on workers of the Company, Although it is true in the workplace there are certain activities that imply a certain complexity for their development, in addition to this the conditions in which they work, the state of the equipment and the knowledge of the personnel, variables that otherwise properly managed, they result in the construction of risk scenarios that negatively affect workers and company productivity. The development of the research allowed the identification of the existing risks in each stage of the production process, the design of an evaluation sheet was implemented, incorporating technical criteria of methodologies such as NPT 330 and GTC40, also through a semi-structure survey The resulting risk levels were identified in the evaluation, and their impact on the integrity of the workers. Finally, the safety guidelines were designed considering the source of the risk, development of the environment and the person. The mechanical and ergonomic risks turned out to be the highest, coinciding with the internal activities carried out, the consequences of which were remorse in the upper extremities of the body, pain due to repetitive and forced postures carried out by the workers. Within the safety guidelines, preventive actions were incorporated with respect to the source of the risk, improvement actions, work environment and continuous training for all personnel.